2009
DOI: 10.1097/nmd.0b013e3181be9c55
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Threats With Weapons

Abstract: The relationship between childhood maltreatment and future threats with weapons is unknown. We examined data from the nationally representative National Comorbidity Survey Replication (n = 5692) and conducted multiple logistic regression analyses to determine the association between childhood maltreatment and lifetime behavior of threatening others with a gun or other weapon. After adjusting for sociodemographic variables, physical abuse, sexual abuse, and witnessing domestic violence were significantly associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 48 publications
1
12
0
Order By: Relevance
“…To elaborate, maltreatment significantly increased the chances of being convicted of a non-violent or a violent adult weapons charge, reinforcing findings from Hygiea, Mota, Afifi, Enns, & Sareen (2009). The study also revealed that maltreatment among CLS participants significantly predicted all adult and lifetime measures of general violence, reinforcing confidence in relations found.…”
Section: Discussionsupporting
confidence: 71%
“…To elaborate, maltreatment significantly increased the chances of being convicted of a non-violent or a violent adult weapons charge, reinforcing findings from Hygiea, Mota, Afifi, Enns, & Sareen (2009). The study also revealed that maltreatment among CLS participants significantly predicted all adult and lifetime measures of general violence, reinforcing confidence in relations found.…”
Section: Discussionsupporting
confidence: 71%
“…We found in a sample of 18-22 year olds that it was associated with moderately large effects on ratings of depression, anger-hostility, dissociation and limbic ‘irritability’, and with very large effect sizes when combined with exposure to other forms of maltreatment (Teicher et al, 2006a). WDV increases risk for depression (Nicodimos et al, 2009) and aggression (Abrahams and Jewkes, 2005; Casiano et al, 2009) by 2-4 fold, and is one of the most common causes of childhood PTSD (Luthra et al, 2009; Silva et al, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…Although many parents try to shelter their children from WDV, children in violent homes commonly see, hear, and intervene in episodes of WDV [2]. WDV increases risk for depression [3] and aggression [4], [5] by 2–4 fold, and is a frequent causes of childhood PTSD [6], [7].…”
Section: Introductionmentioning
confidence: 99%